Pengaruh Model Kulit Bumi terhadap Gelombang ScS dan ScS-ScS - Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2009)
Craniosynostosis, marked by premature fusion of the cranial sutures, leads to abnormal head shapes and possible neurological complications. This report describes a 4-year-and-2-month-old boy diagnosed with pancraniosynostosis who presented with progressive forehead protrusion 11 months after initial cranial suture reconstruction. Whole exome sequencing identified 2 novel compound heterozygous variants in the IL11RA gene (c.673C>T, P. Arg225Trp inherited from the mother and c.728C>G, P. Pro243Arg inherited from the father), both classified as variants of uncertain significance. The patient underwent successful secondary cranial suture reconstruction with favorable 6-month outcomes. These findings expand the mutational spectrum of IL11RA-associated craniosynostosis and highlight the importance of including IL11RA in genetic testing panels for pancraniosynostosis, even in the absence of classic syndromic features.